VALIDATION AND ANALYSIS OF THE KID-KINDL QUESTIONNAIRE IN MALAYSIAN PRIMARY SCHOOL CHILDREN FROM THE CHILDREN’S PERSPECTIVE - Gisely Vionalita; Zalina Ismail (Universitas Muhammadiyah Ponorogo, 2022)
Health-related quality of life (HRQoL), conceptualized as the patient’s evaluations of their health status, is an essential indicator in evaluating health and health care and treating individual patients. The KID-KINDL questionnaire includes four main components: psychological well-being, social relationships, physical functions, and daily activities. This study aims to validate the KID-KINDL questionnaire in the Malay language and measure the HRQOL of Year One students from the children’s perspective. Forward and the Language Centre Universiti Sains Malaysia supervised the backward translation of the KID-KINDL questionnaire. The questionnaire's validation and reliability were assessed with Winstep™ software, using Rasch model statistics. KID-KINDL was applied to 90 Year One students in SK Zainab 2, Kota Bharu, Kelantan. Minor changes were made to the questionnaire after being translated. From the misfit item of those questions, the range to infit and outfit is beyond the acceptable scope for the Likert scale (0.6-1.4), and four questions were deleted in the validated version. Following validation, analysis with Rasch model statistics was carried out. This questionnaire will be used for further in-depth studies on children's health-related quality of life